2022
DOI: 10.3126/jbssr.v7i2.51490
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing Organisational Citizenship Behaviour through Job Characteristics

Abstract: Researchers' contributions in identifying predictors of organisational citizenship behaviours are appreciable, and still, contextual study of job characteristics as an antecedent of enhancing employees' citizenship behaviours will be valuable for the banking and insurance sectors. This study is an endeavour to investigate the way of association and influence of perceived job characteristics on organisational citizenship behaviours (OCBs). Cross-sectional survey data were obtained from 221 employees involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…This finding highlights the importance of addressing job security issues and their impact on organizational employee behavior and commitment. The study's results align with previous research conducted by , which indicated that job instability is associated with decreased individual performance and organizational citizenship behavior (Lee, 2006;Liu et al, 2017;Shahi et al, 2022). In light of the increasingly important role of job security in a highly competitive environment, implementing measures to ensure job security has the potential to foster greater levels of organizational commitment among academic professionals.…”
Section: Discussionsupporting
confidence: 84%
“…This finding highlights the importance of addressing job security issues and their impact on organizational employee behavior and commitment. The study's results align with previous research conducted by , which indicated that job instability is associated with decreased individual performance and organizational citizenship behavior (Lee, 2006;Liu et al, 2017;Shahi et al, 2022). In light of the increasingly important role of job security in a highly competitive environment, implementing measures to ensure job security has the potential to foster greater levels of organizational commitment among academic professionals.…”
Section: Discussionsupporting
confidence: 84%
“…In this sense, green transformation refers to the organizational change towards sustainable and environmentally friendly activities. Businesses and people acknowledge environmental issues' gravity and encourage sustainable operational methods (Robertson & Barling, 2013;Andersson et al, 2013;Pham et al, 2020;Nguyen et al, 2021;Shahi et al, 2022). Promoting dependable production patterns in line with the United Nations' sustainable development goals (SDGs) emphasizes sustainability as an essential component of global social and economic growth (Mouro & Duarte, 2021;Hart & Dowell, 2011).…”
Section: Environmentalmentioning
confidence: 99%
“…Here comes the determining role of managers whose challenge surely remains to make sure to understand every motivational profile they are coping with, so as to provide in a personalized manner what can efficiently and durably motivate each one of them. Motivated individuals are firmly more likely to direct their behaviors towards the expected organizational goals (Shahi et al, 2022).…”
Section: Work Motivationmentioning
confidence: 99%